Safety and Efficacy of Peroral Endoscopic Shorter Myotomy versus Longer Myotomy for Patients with Achalasia: A Systematic Review and Meta-analysis - Han Zhang; Xinyi Zeng; Shu Huang; Huifang Xia; Lei Shi; Jiao Jiang; Wensen Ren; Yan Peng; Muhan Lü; Xiaowei Tang (Gastroenterology Research and Practice)
Background and Aims. The adequate myotomy length during peroral endoscopic myotomy (POEM) is still controversial. We performed this systematic review and meta-analysis to determine the efficacy and safety of the modified POEM with shorter myotomy (SM) and compare the outcomes between SM and longer myotomy (LM) in achalasia patients. Methods. A comprehensive literature search was conducted in PubMed, EMBASE, Cochrane Library, and Web of Science databases from inception to May 28, 2021. The primary outcome was clinical success rate and incidence of reflux-relative adverse events (AEs). Fixed- or random-effect models were adopted for the analysis according to the heterogeneity. Results. Five studies involving 225 patients in SM group and 222 patients in LM group were included. The overall clinical success of SM was 96.6% (95% confidence interval (CI) 92.7 to 98.4%). SM showed noninferior response as compared to LM (risk ratio (RR) 1.02, 95% CI 0.98 to 1.06, P=0.41, I2=0%). Based on the abnormal acid reflux by pH monitoring, its incidence was significantly lower in the SM group than that in the LM group (RR 0.58, 95% CI 0.36 to 0.94, P=0.03, I2=0%). With respect to procedure-related parameters, the total procedure time of SM was significantly shorter than that of LM (mean difference (MD) -16.30, 95% CI -23.10 to -9.49, P<0.001, I2=68%). Conclusions. SM and LM are comparable in providing treatment efficacy for achalasia patients, whereas less operation time and lower incidence of post-POEM abnormal esophageal acid exposure are observed in SM.